Weight and Body Composition Changes during the First Three Years of College - Sareen S. Gropper; Karla P. Simmons; Lenda Jo Connell; Pamela V. Ulrich (Hindawi Limited, 2012)
Differences in weight, body mass index (BMI), percent and absolute body fat, fat-free mass, and waist circumference were investigated in a group of males and females during the first three years (from 2007 to 2010) of college. Significant three-year gains were observed for weight 2.1±4.7 kg, BMI 0.7±1.6 kg/m2, percent body fat 2.7±3.3%, and fat mass 2.3±3.5 kg. A significant loss of fat-free mass, −0.5 kg, was observed among females. Absolute gains in weight, BMI, and percent and absolute body fat were highest during the freshman year, followed by the junior year, and lowest during the sophomore year. Among the 70% of students gaining weight over the three years, weight gain averaged 4.3 kg. The numbers of females with over 30% body fat doubled, and the number of males with over 20% body fat increased fivefold. Initially 15% of students were classified as obese/overweight and 79% normal weight; by the end of the junior year, 24% were obese/overweight and 70% were normal weight. Efforts on college campuses to promote healthy lifestyles among its student population are needed throughout the college years.